2020
DOI: 10.14311/app.2020.27.0057
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Surface Acoustic Waves for Thin Film Characterization

Abstract: Knowledge of mechanical properties of thin films is essential for most of their applications. However, their determination can be problematic for very thin films. LAW (Laser-induced acoustic waves) is a combined acousto-optic method capable of measuring films with thickness from few nanometers. It utilizes ultrasound surface waves which are excited via short laser pulses and detected by a PVDF foil. Properties such as Young’s modulus, Poisson’s ratio and density of both the film and the substrate as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…A nanotemplate radius r tem = 2 nm was assumed and the resulting curves for different plausible Young's moduli are plotted. For the Young's modulus of SiO 2 , various values have been reported in literature, from 10 − 40 GPa [55], up to 100 GPa [56]. For thin film HfO 2 values up to 180 GPa have been reported [57].…”
Section: Mechanical Stressmentioning
confidence: 99%
“…A nanotemplate radius r tem = 2 nm was assumed and the resulting curves for different plausible Young's moduli are plotted. For the Young's modulus of SiO 2 , various values have been reported in literature, from 10 − 40 GPa [55], up to 100 GPa [56]. For thin film HfO 2 values up to 180 GPa have been reported [57].…”
Section: Mechanical Stressmentioning
confidence: 99%
“…Previous researches reported that the tensile properties of the SiO 2 film, utilizing various methods such as nanoindentation, , bulge test, beam bending, , resonance frequency, phase velocity measurement, and Brillouin spectral analysis, have been reported. The CTE of the SiO 2 film was measured via curvature difference resulting from residual stress due to CTE mismatch with the substrate. ,, The presence of the substrate makes it difficult to measure the intrinsic thermomechanical properties of SiO 2 thin films using these methods.…”
Section: Introductionmentioning
confidence: 99%